The prognostic significance of aldehyde dehydrogenase 1A1 (ALDH1A1) and CD133 expression in early stage non-small cell lung cancer. Issue 12 (22nd July 2013) - Alamgeer, Muhammad; Ganju, Vinod; Szczepny, Anette; Russell, Prudence A; Prodanovic, Zdenka; Kumar, Beena; Wainer, Zoe; Brown, Tracey; Schneider-Kolsky, Michal; Conron, Matthew; Wright, Gavin; Watkins, D Neil
Abstract : Background: Expression of aldehyde dehydrogenase 1A1 (ALDH1A1) and CD133 has been functionally associated with a stem cell phenotype in normal and malignant cells. The prevalence of such cells in solid tumours should therefore correlate with recurrence and/or metastasis following definitive surgical resection. The aim of this study was to evaluate the prognostic significance of ALDH1A1 and CD133 in surgically resected, early stage non-small cell lung cancer (NSCLC). Methods: A retrospective analysis of ALDH1A1 and CD133 expression in 205 patients with pathologic stage I NSCLC was performed using immunohistochemistry. The association between the expression of both markers and survival was determined. Results: We identified 62 relapses and 58 cancer-related deaths in 144 stage 1A and 61 stage 1B patients, analysed at a median of 5-years follow-up. Overexpression of ALDH1A1 and CD133, detected in 68.7% and 50.7% of primary tumours, respectively, was an independent prognostic indicator for overall survival by multivariable Cox proportional hazard model (p=0.017 and 0.039, respectively). Overexpression of ALDH1A1, but not of CD133, predicted poor recurrence-free survival (p=0.025). When categorised into three groups according to expression of ALDH1A1/CD133, patients with overexpression of both ALDH1A1 and CD133 belonged to the group with the shortest recurrence-free and overall survival (p=0.015 and 0.017, respectively). Conclusions: Expression of ALDH1A1 and CD133, and coexpression of ALDH1A1 and CD133, is strongly associated with poor survival in early-stage NSCLC following surgical resection. These data are consistent with the hypothesis that expression of stem cell markers correlates with recurrence as an indirect measure of self-renewal capacity.